2019
DOI: 10.1111/nuf.12329
|View full text |Cite
|
Sign up to set email alerts
|

Reaching out: Organizational structures and public communication of nursing professional associations and trade unions in Portugal

Abstract: Aim: To describe the organizational structure and resources for strategic mediacommunication of nursing professional associations and trade unions in Portugal.Design and Methods: Quantitative study, with a cross-sectional, exploratory/ descriptive design. From October to November 2017, a questionnaire was sent to 21 nursing professional associations and trade unions in Portugal. Eleven (52.4%) organizations replied: nine professional associations and two trade unions.Results: The participating organizations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(36 reference statements)
0
6
0
1
Order By: Relevance
“…Hemşirelik okulları, sendikalar, dernekler ve sağlık kurumlarının bu anlamda iş birliği içerisinde olması önem arz etmektedir. 23,24 Uluslararası literatürde hemşirelik derneklerinin işleyişleri ve faaliyetleri incelendiğinde, hemşirelerin iş yükünün azaltılması eşitsizliklerin ortadan kaldırılması, profesyonel konularda farkındalığın arttırılması, işle ilgili sorunların paylaşımının sağlanması, çözüm önerilerinin oluşturulması, mesleki gelişim ve sosyalleşmenin sağlanması, eğitim fırsatlarının sağlanması, mesleki sigorta oluşturulması, akademik araştırmalarda ödenek sağlanması, yasal olarak hakların savunuculuğunun yapılması ve ortak ağ oluşturularak bilgi paylaşımın yapılması gibi faaliyetler sıralanmaktadır. 13,24,25 Uluslararası kapsamda dernek işleyişlerine İran örneği ile bakıldığında, hemşirelik dernekleri İran Anayasasına göre kurulmuş sivil toplum örgütleri olduğu ve hemşirelik ile ilgili düzenlemelerin kontrolü sağlık bakanlığı aracığı ile yapıldığı, birçok ülkede olduğu gibi İran'da da mesleki derneklere üyelik isteğe bağlı ve yasal olarak zorunlu olmadığı bilgisine ulaşılmıştır.…”
Section: Discussionunclassified
“…Hemşirelik okulları, sendikalar, dernekler ve sağlık kurumlarının bu anlamda iş birliği içerisinde olması önem arz etmektedir. 23,24 Uluslararası literatürde hemşirelik derneklerinin işleyişleri ve faaliyetleri incelendiğinde, hemşirelerin iş yükünün azaltılması eşitsizliklerin ortadan kaldırılması, profesyonel konularda farkındalığın arttırılması, işle ilgili sorunların paylaşımının sağlanması, çözüm önerilerinin oluşturulması, mesleki gelişim ve sosyalleşmenin sağlanması, eğitim fırsatlarının sağlanması, mesleki sigorta oluşturulması, akademik araştırmalarda ödenek sağlanması, yasal olarak hakların savunuculuğunun yapılması ve ortak ağ oluşturularak bilgi paylaşımın yapılması gibi faaliyetler sıralanmaktadır. 13,24,25 Uluslararası kapsamda dernek işleyişlerine İran örneği ile bakıldığında, hemşirelik dernekleri İran Anayasasına göre kurulmuş sivil toplum örgütleri olduğu ve hemşirelik ile ilgili düzenlemelerin kontrolü sağlık bakanlığı aracığı ile yapıldığı, birçok ülkede olduğu gibi İran'da da mesleki derneklere üyelik isteğe bağlı ve yasal olarak zorunlu olmadığı bilgisine ulaşılmıştır.…”
Section: Discussionunclassified
“…Of the 11 associations participating in the first phase of the research (21) , those that had interacted frequently with the media were selected. Of the six associations representing different areas (professional regulation, defense of labor rights, and professional specialization), five agreed to participate.…”
Section: Data Sourcementioning
confidence: 99%
“…In addition to media attention, it is intended to increase the importance of the association in the eyes of journalists and the public (standing) and obtain a favorable framing (preferred framing) of messages to be communicated (12) . Research produced in recent years have revealed: the scarce media coverage of the profession, with nurses being news sources in 1.5% to 6.6% of the total published health related news (7,(16)(17)(18) ; the media discourse tending to be negative, focusing on work problems, the shortage of nurses, and scandals in the profession (5,11,16,19) ; the reduced frequency of nurses' interaction with mass media (20) ; the existence of limited resources (reduced number of members and funding), the lack of formal communication structures, such as communication offices or spokespersons trained to interact with the media; and the spread of a discourse centered on professionals and little directed at citizens (21) .…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are an important part of the healthcare system and predominantly involved in direct patient care. Therefore, nursing organizations are also highly important and have developed in national and international spheres over the recent years 3 . The number of nursing organizations and nurses, who are members of such organizations is currently on the increase in the United States and, hence, their implications to the nursing profession is becoming more evident 4 …”
Section: Introductionmentioning
confidence: 99%
“…Each organization is unique. Nonetheless, they are alike in creating a unified voice and enhancing the working conditions of nurses 3 …”
Section: Introductionmentioning
confidence: 99%